A lei 11.274/2006 e o trabalho pedagógico com criança de seis anos no ensino fundamental na cidade de Farias Brito-CE - Souza, Cicera Cosmo de (2018)
The following thesis has the guiding questions: what is the basis of the pedagogical work of the teachers from 1st grade of elementary school? How did the State of Ceará and Farias Brito city adjust the norms and educational guidelines by defining new arrangements and educational politics? How is the organization of the pedagogical work in the process of implantation of Primary School of nine years with the insertion of the six-year-old child in Elementary School in the Farias Brito City, State of Ceará? Aiming to answer such questions, we aim, across the board, to analyze the organization and realization of the pedagogical work with children of six-years-old in Elementary School, under the Law 11,274 of February 6th, 2006. As way of considerations, we realized that children and childhood, although inseparable, have different meanings. The first concerns about biological issues, while the second is a social, cultural and historical construction. The Brazilian educational politics reflects the conjuncture that they are inserted, the Law number 11. 274/2006 isn’t an exception, since it carries with it the marks of political and economic control exercised by neoliberalism. These issues directly reflect the pedagogical work accomplished with sixyears-old children in the first year of Elementary School, the focus on literacy neglects the other formative aspects particular to childhood.